Cultivation of the ideal body : how advertisements affect women and their body perceptions - Lam, Racheal Lai Yee (2010)
A woman's idea of a perfect body shape is the result of the interplay of several factors which eventually contributes to the cultivation of an idealized concept on the image of her body. With the recent rising trends of women joining fitness clubs membership, I am keen to discover if social demographics such as age and occupation of these women have affected their decision in joining a fitness club. The predominant focus of this study revolves around women of different ages and occupations and their motivations in visiting fitness clubs. To understand these motivations, this study also seeks to discern the varying degree of influences which the advertising media have upon women's decisions to join a fitness club. Therefore, this study also focuses on examining the local media to gain an understanding of the social, cultural, economic, and political influences which contribute into shaping these motivations.